PENGARUH KOORDINASI PIMPINAN TERHADAP KINERJA PEGAWAI KECAMATAN KESAMBI KOTA CIREBON - Eka Wildanu; Agus Irfan; Dikhorir Afnan; Imron Fauzi (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2021)
This study aims to sense the excesses of the classification of guidance on the capabilities of workers in Kesambi District, Cirebon City. Coordination is not one particle slack fault in the worker's performance, but added classification is one particle fault that strengthens the worker's capability. The results of the examination show that the average classification of guidance is 4.36, which indicates that the close leadership coordination in Kesambi District, Cirebon City is good. Based on a factual experiment that explores the effect of guiding classification on the ability of workers to reach the estimated effect of Adjusted R square, the coefficient of linear effect plus perspective on life is .055 containing the causes of Leadership Coordination to put excesses on Employee Performance in Kesambi District, Cirebon City. The contribution of the influence is 55%. While the remaining 45% was caused by other causes that were not studied. The t-estimated outlook on life is 1,708 plus Sig's outlook is .094. This sura aims that the outlook t is more likely to be close to the 2009 sequence t and the outlook of Sig is more designed to be near 0.05.